2014
DOI: 10.1002/chem.201304094
|View full text |Cite
|
Sign up to set email alerts
|

Triggered Liposomal Release through a Synthetic Phosphatidylcholine Analogue Bearing a Photocleavable Moiety Embedded within the sn‐2 Acyl Chain

Abstract: Liposomes represent promising carriers for drug delivery applications. To maximize this potential, there has been significant interest in developing liposomal systems encapsulating molecular cargo that are highly stable until their contents are released remotely in a controlled manner. Herein, we describe the design, synthesis, and analysis of a photocleavable analogue of the ubiquitous lipid phosphoatidylcholine (PC) for the development of highly stable and controllable photodisruptable membranes. Our strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 48 publications
3
29
0
Order By: Relevance
“…As can be seen from the results shown in Figure A, we observed a gradual decrease in nile red fluorescence upon titration with calcium that was dependent on the percentage of 1 in liposomes. Results from control liposomes lacking 1 indicated a background fluorescence decrease of ≈10 %, which is in line with previous work . This was enhanced to ≈25 % decrease with liposomes containing 3 % of 1 , ≈50 % with 5 % of 1 , and ≈65 % with 10 % of 1 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As can be seen from the results shown in Figure A, we observed a gradual decrease in nile red fluorescence upon titration with calcium that was dependent on the percentage of 1 in liposomes. Results from control liposomes lacking 1 indicated a background fluorescence decrease of ≈10 %, which is in line with previous work . This was enhanced to ≈25 % decrease with liposomes containing 3 % of 1 , ≈50 % with 5 % of 1 , and ≈65 % with 10 % of 1 .…”
Section: Resultssupporting
confidence: 91%
“…Following the synthesis, we set out to evaluate triggered release from liposomes incorporating 1 by conducting fluorescence release assays employing the dye, nile red. Nile red is a hydrophobic fluorophore that is solubilized by encapsulation within liposome bilayers, and therefore mimics the properties of commonly used non‐polar drugs . This leads to a standard fluorescence signal for the dye when solubilized by the liposomes.…”
Section: Resultsmentioning
confidence: 99%
“…Bayer et al reported the synthesis of a new photocleavable phospholipid, namely NB‐PC . Stable NB‐PC liposomes were generated from the modification of the natural occurring phosphatidylcholine (PC) to include 2‐nitrobenzyl in the acyl chain at the sn ‐2 position.…”
Section: Mechanisms Of Light‐triggered Release From Liposomesmentioning
confidence: 99%
“…(B) Nile red is released from the bilayer after NB‐PC photolysis. Figure used with permission from the publisher…”
Section: Mechanisms Of Light‐triggered Release From Liposomesmentioning
confidence: 99%
“…38 Prior work involving the incorporation of photocleavable groups into lipids has focused on light-initiated release of molecules from liposomes. 3945 In these cases, molecules such as drugs have been non-covalently encapsulated in the liposome and release was stimulated by decomposition or disruption of the membrane. However, noncovalent molecular encapsulation can suffer from background leakage, and thus it may be preferable to covalently attach target molecules to lipids prior to triggering the release through bond cleavage.…”
Section: Introductionmentioning
confidence: 99%